I‐PET score: Combining whole body iodine and 18F‐FDG PET/CT imaging to predict progression in structurally or biochemically incomplete thyroid cancer. (15th August 2022) - Wijewardene, Ayanthi; Hoang, Jeremy; Maw, Aung Min; Gild, Matti; Tacon, Lyndal; Roach, Paul; Schembri, Geoffrey; Chan, David; Clifton‐Bligh, Roderick
Abstract: Objective: We propose a new scoring system (I‐PET) combining whole body scan (WBS) and FDG findings to identify patients who have or are likely to become refractory to radioactive iodine. Design: Retrospective analysis of 142 patients age >18 with differentiated thyroid cancer who had a F‐18 labelled fluoro‐2‐deoxyglucose ( 18 F‐FDG) positron emission tomography (PET) and WBS within a 6‐month period between 2010 and 2020. Pairs of 18 F‐FDG PET and WBS were reviewed by three independent nuclear medicine physicians and an I‐PET score was assigned: I‐PET [0] : Iodine −ve/FDG −ve, I‐PET [1] : Iodine +ve/FDG −ve, I‐PET [2] : Iodine +ve/FDG +ve and I‐PET [3] : Iodine −ve/FDG +ve. Patients with FDG +ve lesions (I‐PET [2] and I‐PET [3]) were further classified into groups A and B if SUVmax was ≤5 or >5, respectively. Follow‐up data were obtained by chart review. Progression was defined as structural progression as per RECIST 1.1 or further surgical intervention; or biochemical progression as unstimulated thyroglobulin increasing >20% from baseline. Results: Of 142 patients included in the study 121 patients had follow‐up data available for review. At baseline, 49 patients were classified as I‐PET [0], 10 as I‐PET [1], 16 as I‐PET [2] and 46 as I‐PET [3]. Progression was seen in 11/49 (22%) of I‐PET [0], 4/10 (40%) of I‐PET [1], 10/16 (63%) of I‐PET [2] and 34/46 (74%) of I‐PET [3] ( p < 0.001). I‐PET [2B] and I‐PET [3B] had a progression rate of 88% (7/8) and 78% (25/32), respectively. I‐PET [3B] were 9.6 times more likely to commence multikinase inhibitor therapy ( p = 0.001) and had 8 times greater mortality ( p = 0.003) than patients in other I‐PET groups combined. Conclusion: I‐PET is a simple readily acquired imaging biomarker that potentially enhances the dynamic risk stratification and guide treatment in thyroid cancer.